Isolation and identification of Klebsiella pneumonia from wound infections and study of the synergistic effect of carpenems and cefepime - Qasim, Ali; Hind Abdullah Salih (University of Thi-Qar Journal of Science, 2024)
Surgical site infection (SSI) is a major source of morbidity and mortality in developing countries despite recent advances in sterile techniques. We studied antibiotics through their effect on bacterial pathogens isolated from wound infections singly and synergistically, which were observed in hospitals in Dhi Qar Governorate. These bacteria, Klebsiella pneumoniae 300 clinical samples were collected from Al-Hussein Teaching, Nasiriya Teaching and Al-Haboubi Teaching Hospitals in Dhi Qar Governorate for the period from September - December 2023. The results showed the presence of 16 bacterial isolates belonging to K. Pneumonia. Statistical and descriptive analysis was performed using chi-square. The rates of antibiotic resistance varied through the use of 4 types of carpenems and one type of cephalosporins. The resistance rate to meropenem alone was 6 (37.5%), while the resistance rate was higher for meropenem synergistically with Imipenem, Ertapenem, Doripenem, and cefepime, 7 (43.8%), respectively. In case of synergy the resistance rate was as to Imipenem, 7 (43.8) alone, while in synergy, the resistance rate was lower for Imipenem with cefepime, Ertapenem, and Doripenem, 5 (29.4%), 5 (31.3%), 6 (37.5%), respectively the resistance rate for synergy was highest than cefepime which was 11 (68.8) alone, while synergistically the resistance rate was lower for cefepime with Ertapenem and Doripenem 7 (38.9%), 7 (43.8%) respectively. While resistance to Ertapenem was higher than Doripenem 9 (56.3) and 7 (43.8), respectively, alone and synergistically, the resistance rate was lower for Ertapenem with Doripenem 5 (31.3%). This study revealed that taking two synergistic